Exploring Pinus nigra's induced defense arsenal against Diplodia sapinea through gene and metabolic pathway analysis - Trujillo-Moya, Carlos; Olsson, Sanna; Mottinger-Kroupa, Susanne; Halmschlager, Erhard; Ertl, Reinhard; Gailing, Oliver; Vornam, Barbara; Fady, Bruno; Ganthaler, Andrea; Ahmad, Muhammad; Espinosa-Ruiz, Ana; Carrera, Esther; et al. (BioMed Central, 2026)
The European black pine (Pinus nigra J. F. Arnold) is a conifer of high economic and ecological importance and is considered a potential alternative to several forest tree species in Central Europe to support adaptation to global climate warming. However, the fungus Diplodia sapinea (Fr.) Fuckel is causing severe damage and world-wide economic loss to this and other Pinus host species. The lack of genomic resources and the scarce knowledge of the tree´s molecular defense mechanisms limit any breeding perspectives. Here, we report the results of a controlled infection experiment in which the transcriptomic and metabolomic profiles of mock and infected P. nigra saplings from two provenances were compared over a period of 21 days. This combined approach suggests that P. nigra response to D. sapinea infection is activated between 8 and 21 days post-inoculation when key plant defense signaling hormones such as jasmonic acid, abscisic acid and salicylic acid increased. This concurred with high differential gene expression, including the activation of major plant defense-related pathways, leading to the induction of several phytoalexins and defense-related proteins. Furthermore, some of these responses were provenance-specific. Finally, this study identified key genes and metabolic pathways involved in the defense response of P. nigra to D. sapinea, providing a solid basis for further exploration of genetic variation among natural populations (provenances) of different subspecies with varying constitutive and induced defense responses. This deeper understanding will aid in elucidating resistance mechanisms and guiding the selection of plant reproductive material for future forest plantations.
Keywords: conifers; black pine; Diplodia tip blight; transcriptomics; metabolomics; plant defense response; plant hormones; phenolics; terpenoids; plant-pathogen interaction